Quantitative PCR as a predictor of aligned ancient DNA read counts following targeted enrichment. (December 2013) - Enk, Jacob; Rouillard, Jean-Marie; Poinar, Hendrik
Targeted DNA enrichment through hybridization capture (EHC) is rapidly replacing PCR as the method of choice for enrichment prior to genomic resequencing. This is especially true in the case of ancient DNA (aDNA) from long-dead organisms, where targets tend to be highly fragmented and outnumbered by contaminant DNA. However, the behavior of EHC using aDNA has been quite variable, making success difficult to predict and preventing efficient sample equilibration during multiplexed sequencing runs. Here, we evaluate whether quantitative PCR (qPCR) measurements of aDNA samples correlate with on-target read counts before and after EHC. Our data indicate that not only do simple target qPCRs correlate strongly with high-throughput sequencing (HTS) data but that certain sample characteristics, such as overall target abundance as well as experimental parameters (e.g., bait concentration and secondary structure propensity), consistently influenced enrichment of our diverse set of aDNA samples. Taken together, our results should help guide experimental design, screening strategies, and multiplexed sample equilibration, increasing yield and reducing the expected and actual cost of aDNA EHC high-throughput sequencing projects in the future.